1998
DOI: 10.2527/1998.76123034x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extrusion processing of carbohydrate sources on weanling pig performance.

Abstract: Three experiments were conducted to study the effects of extrusion processing on growth performance of weanling pigs. In Exp. 1, 350 weanling pigs (initially 4.4 +/- 1.0 kg BW and 10 +/- 2 d of age) were used to study the effects of various carbohydrate sources (corn, cornstarch, broken rice, wheat flour, and grain sorghum), with or without moist extrusion processing, on growth performance in a 5 x 2 factorial arrangement of treatments. No carbohydrate source x extrusion processing interactions were observed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 17 publications
5
34
1
3
Order By: Relevance
“…Nevertheless significant increases in feed intake together with improved growth have been reported in complex diets compared with simple diets (Dritz et al 1996;Mavromichalis et al 2001;Wolter et al 2003;Mahan et al 2004). On the other hand, rice was highly preferred to corn in nursing pigs (Sola`-Oriol et al 2005) and weanling pigs fed a corn-based diet had significantly poorer feed intake and growth than those fed a rice-based diet (Hongtrakul et al 1998;Vicente et al 2008). Thus, we hypothesize that the increases in feed intake could explain most of the improved performance and that feed palatability may play a central role in increasing meal size and frequency particularly in early weaned young animals.…”
Section: Comparative Oral Somatosensingmentioning
confidence: 93%
“…Nevertheless significant increases in feed intake together with improved growth have been reported in complex diets compared with simple diets (Dritz et al 1996;Mavromichalis et al 2001;Wolter et al 2003;Mahan et al 2004). On the other hand, rice was highly preferred to corn in nursing pigs (Sola`-Oriol et al 2005) and weanling pigs fed a corn-based diet had significantly poorer feed intake and growth than those fed a rice-based diet (Hongtrakul et al 1998;Vicente et al 2008). Thus, we hypothesize that the increases in feed intake could explain most of the improved performance and that feed palatability may play a central role in increasing meal size and frequency particularly in early weaned young animals.…”
Section: Comparative Oral Somatosensingmentioning
confidence: 93%
“…Weurding et al (2003) and Van Kempen et al (2007) also reported that raw corn was preferred for animal feeding due to its slowly digestible starch resulting in a slow and steady release of glucose which did not strongly stimulate insulin, therefore raw corn could improve feed intake and performance. In addition, the reason for the lower feed intake in extruded corn may be due to the poorer palatability caused by higher levels of retrograded starch (Hongtrakul et al, 1998;Lv et al, 2006) compared with raw corn. Another reason for the lower feed intake in extruded corn is that the starch in extruded corn had the fastest rate of digestion and resulted in a higher blood glucose which affects satiety.…”
Section: Discussionmentioning
confidence: 99%
“…It is a versatile technique that is already used routinely in the human food industry to produce starch materials with very specific physico-chemical properties, in a reproducible manner. Although studies examining the use of extrusion processing in weaned piglet diets appear to give somewhat mixed conclusions (10,15) , it is possible that at least some of this disparity may originate from a misconception about the amount of starch conversion resulting from the processing method. This is illustrated by the fact that processing variables are rarely cited in the published literature, making comparison between studies difficult.…”
Section: In Vitro Differences Between Dietsmentioning
confidence: 99%